An In-Silico Exploration of Fluoroindazole Derivatives as Perspective Anti-Alzheimer Disease (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Alzheimer disease (AD) is the most common type of dementia, is an irreversible neurodegenerative disease, accounting for at least two-thirds of cases of dementia in people age 65 and older. Fluoroindazole scaffolds are specialized heterocyclic organic compounds featuring a fluorine atom attached to an indazole ring system, widely utilized in drug discovery as anti-Alzheimer, kinase inhibitors and anti-inflammatory agents. In the present study we use a comprehensive approach by integrating network pharmacology, molecular docking techniques to explore the fluoroindazole derivatives against AD. Totally 307 compounds were retrieved from PubChem and they were subjected to physiochemical, pharmacokinetic, metabolic and toxicity profiles. The compounds which are having good pharmacokinetic and less toxicity profile were selected for further studies. A total of twelve compounds were finalized. Top ten targets were identified using CytoHubba plugin in Cytoscape. Among the top targets the most significant targets namely, PIK3CA, AKT1 and EGFR were selected for docking studies. Molecular docking was performed using Mz-Dock tool with Autodock Vina mode. Molecular docking studies revealed that the compound 2- (3,4-dihydroisoquinolin-6-yl)-5-fluoroindazole-7-carboxamide showed good binding energy and interaction profile. In conclusion our study revealed that fluoroindazole derivatives produce promising action for AD.
Keywords: Alzheimer disease; fluoroindazole; In silico study; pharmacology and molecular docking